2019
DOI: 10.1051/e3sconf/201913101040
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal changes of NDVI and correlation with meteorological factors in northern china from 1985-2015

Abstract: The NDVI in northern china is vulnerable and is greatly affected by meteorological factors. In this study, the correlation between changes of NDVI and the major meteorological factors (temperature, precipitation) in northern China in the past 30 years with Trend analysis and partial correlation analysis methods. The results show that: (1) In the recent 30 years, the annual average NDVI in northern China shows an upward trend of volatility, with an annual growth rate of 0.0015, and the overall vegetation covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Some studies have also concluded that there is a correlation between PWV and NDVI [45][46][47]. Some studies have also found that there is a correlation between precipitation and NDVI [48][49][50][51][52], which indirectly proves the correlation between PWV and NDVI. However, the specific change trend of the correlation between PWV and NDVI is different due Some studies have also concluded that there is a correlation between PWV and NDVI [45][46][47].…”
Section: Influence Of Extreme Climate On Vegetation Growthmentioning
confidence: 96%
See 1 more Smart Citation
“…Some studies have also concluded that there is a correlation between PWV and NDVI [45][46][47]. Some studies have also found that there is a correlation between precipitation and NDVI [48][49][50][51][52], which indirectly proves the correlation between PWV and NDVI. However, the specific change trend of the correlation between PWV and NDVI is different due Some studies have also concluded that there is a correlation between PWV and NDVI [45][46][47].…”
Section: Influence Of Extreme Climate On Vegetation Growthmentioning
confidence: 96%
“…However, the specific change trend of the correlation between PWV and NDVI is different due Some studies have also concluded that there is a correlation between PWV and NDVI [45][46][47]. Some studies have also found that there is a correlation between precipitation and NDVI [48][49][50][51][52], which indirectly proves the correlation between PWV and NDVI. How- The distribution of NDVI variation compared to the last year in August for the period of 2008 to 2015 is presented in Figure 13, from which it can be observed that the NDVI values in 2014 decreased in the northern part while increased in the southern part of Zhejiang province.…”
Section: Influence Of Extreme Climate On Vegetation Growthmentioning
confidence: 99%
“…The mean NDVI was calculated to detect the vegetation variation and its relation to climate change. Spatiotemporal changes of NDVI was studied by Pan et al [8]. Their result show that the annual average of NDVI has an upward trend in northern China.…”
Section: Introductionmentioning
confidence: 98%
“…With the development of remote sensing technology, many high resolution images were used for tea plantation extraction [6,7]. In previous studies, many scholars have studied surface vegetation coverage at different spatial and temporal scales [4] based on time series data and spatiotemporal changes of NDVI [8]. Ning et al [4] analyzed temporal and spatial changes of NDVI and explored the impacts of human activities on the observed NDVI changes on the northern Loess Plateau.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation